Transformasi Pendidikan Sebagai Pilar Kebangkitan Warga Komunitas: Telaah dari Al-Imran 3:113 - Yessi Handriyani; Hamim Ilyas (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The purpose of writing this work is the urgency of education as education for community members, community education and the meaning of honesty based on Surah Ali Imran 3:123, as well as the foundations of virtue in the community and the wisdom of honesty in the community in Islam. This research is a literature study that focuses on analyzing the concept of educational transformation in community members by referring to the verse Ali Imran 3:113. Data was obtained through library studies of the Al-Qur'an, educational literature, as well as analysis of relevant educational policy documents, then analyzed descriptively to understand the role of education in changing communities. Community-based education is a necessity in forming good character, facing moral challenges, and promoting lifelong learning, especially in the Islamic context which emphasizes unity and religious values. b) Surah Ali Imran 3:123 emphasizes the importance of education based on religious and moral values in forming the character and awareness of the Muslim community, making it a strong foundation for the development of a superior community. c) Surah Ali Imran 3:113 highlights honesty and moral values as key foundations in community education, creating strong character, a transparent environment, and support for justice. d) The wisdom of honesty in communities in Islam is that honesty leads individuals to heaven, builds trust, and forms a strong moral foundation in the community, so that it becomes a core value in Islamic community education.